2005
DOI: 10.1381/0960892055002239
|View full text |Cite
|
Sign up to set email alerts
|

Changes in Liver Histology Accompanying Massive Weight Loss after Gastroplasty for Morbid Obesity

Abstract: NASH improved significantly with massive weight loss in non-diabetic, non-alcoholic, morbidly obese subjects, while fibrosis improved in nearly half of the patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
64
1
9

Year Published

2007
2007
2022
2022

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 120 publications
(75 citation statements)
references
References 31 publications
1
64
1
9
Order By: Relevance
“…In the current study, 85% of the subjects were associated with NASH reported more scarcely in previous studies (14,(25)(26)(27)(28). This difference of prevalence is discussed further.…”
Section: Discussioncontrasting
confidence: 41%
“…In the current study, 85% of the subjects were associated with NASH reported more scarcely in previous studies (14,(25)(26)(27)(28). This difference of prevalence is discussed further.…”
Section: Discussioncontrasting
confidence: 41%
“…[115][116][117][118][119][120][121][122][123][124][125][126][127][128][129][130][131][132][133] A schematic representation of the search in the online databases and the identification, exclusion and selection of the articles is presented in Figure 1.…”
Section: Resultsmentioning
confidence: 99%
“…It has been proven that lifestyle modification and regular physiological exercise will regulate the individual's body weight and improve NASH and the associated metabolic syndrome [3][4][5] . However, if there is no change in the course of disease after adequate lifestyle changes, pharmacological interventions should be considered, especially for those patients at a high risk of progression.…”
Section: Introductionmentioning
confidence: 99%